Effects of Digital Video Instructional Strategy on Students’ Achievement and Retention in Basic Science - OSUAFOR , Abigail M.; OBILI, Melody O. (Socialscientia: Journal of Social Sciences and Humanities, 2021)
The study investigates the Effect of Digital Video Instructional Strategy on Students’ Achievement and Retention in Basic Science. Two research questions and two hypotheses guided the study. Quasi-experimental non-equivalent control design was adopted for the study. The study was carried out in Awka Education Zone of Anambra State. The population for the study was 2,694 JS II students from 15 government-owned co-educational secondary schools in Awka Education zone of Anambra State. The sample size for the study was 92 (39 males and 53 females) JSII students selected through balloting sampling. A 40 item multiple choice question of BSAT was the instrument used to collect data. A digital video instructional package was developed for the experimental group. Mean and standard deviation were used to answer the research questions and ANCOVA was used to test the null hypotheses at 0.05 level of significance. The findings revealed that students taught using Digital Video Instructional Strategy (DVIS) achieved and retained more than those taught with lecture method. Based on the findings, it was recommended among others that the use of DVIS should be embraced by teachers to convey their instruction in classroom since it has been found to be effective in basic science students’ achievement and retention.